The Kingfisher animal encyclopedia - Burnie, David (New York : Kingfisher, 2011)
Provides an overview of topics related to animal life, such as classification, communication, habitats, and migration; and contains profiles of more than two thousand species of animal, including scientific name, distribution, size, and brief descriptions for each.
Includes index.
Includes index.
8.2
3-6
3-6
Keywords: Animals -- Encyclopedias, Juvenile; Animals -- Encyclopedias; Animals -- Encyclopedias